Patient-reported outcomes: the ICHOM Standard Set for Inflammatory Bowel Disease in real-life practice helps quantify deficits in current care - Wong, D; Matini, L; Kormilitzin, A; Kantschuster, R; Simadibrata, DM; Lyden, S; Wilson, J; Brain, OA; Palmer, R; Ambrose, T; Satsangi, J; South, M; et al. (Oxford University Press, 2022)
Background: Patient-reported outcome measures [PROMs] are key to documenting outcomes that matter most to patients and are increasingly important to commissioners of health care seeking value. We report the first series of the ICHOM Standard Set for Inflammatory Bowel Disease [IBD].